SURVIVAL STRATEGIES OF SMES: AN APPROACH OF STATISTICAL QUALITY CONTROL METHODS - Kazeem, Kolawole R.; Olufemi, Olugbenga P.; Nofiu, Tunji N. (FUDMA Journal of Sciences, 2025)
A wealth of literature exists on benefits of SMEs to an economy. These include: creation of jobs, reducing income disparities, the development of skilled and semi-skilled workers for future industrial expansion and excellent breeding ground for entrepreneurial and managerial talents. The critical shortage of these benefits is often a barrier to economic development. To stimulate processes of qualitative growth in SMEs, this study investigated the application and effective use of Statistical Quality Control (SQC) tools in entrepreneur firms. The results showed that most managers are still experiencing low levels of quality control implementation and they do not recognize the need to compete in the pursuit of modern technologies. This could be due to the major problems of SMEs such as knowledge loss, human and financial resource limitation, product design and development incapability, lack of training infrastructure and networking. There is a growing need for advanced and codified quality control practices.